Reintroduction of cow's milk in milk-allergic children: safety and risk factors - Vassilopoulou, E.; Konstantinou, G.; Kassimos, D.; Douladiris, N.; Xepapadaki, P.; Manoussakis, E.; Saxoni-Papageorgiou, P.; Papadopoulos, N. G. (Int Arch Allergy Immunol, 2008)
Although development of clinical tolerance is the rule in allergy to cow's milk (CM), food challenges are required in order to reintroduce CM into the patient's diet. Less 'invasive' procedures able to predict tolerance would be useful as clinical tools. The purpose of this study was to identify potential risk factors for clinical reactivity in CM-allergic children assessed for CM reintroduction.|One hundred and sixteen open challenges performed in children 10-47 months old with IgE-mediated allergy to CM, in order to reintroduce CM into the diet, were retrospectively evaluated. Specific IgE (sIgE) levels assessed by the CAP System FEIA and skin prick tests (SPT) were obtained at diagnosis and prechallenge. Demographic parameters and measures of sIgE were evaluated as potential predictors of a positive challenge in univariate and multivariate logistic regression models.|Twenty-four out of 116 challenges were positive, 9 of which required the use of adrenaline. In order of performance, prechallenge sIgE <3.94 kU/l, the combination of SPT and sIgE or an SPT wheal <4 mm could correctly predict a negative challenge outcome, whereas values of SPT >7.5 mm or sIgE >25.4 kU/l, or their combination, had a high positive predictive value. The presence of atopic dermatitis did not affect the predictive accuracy of these values.|Milk sIgE level prechallenge is a useful predictor of challenge outcome in patients with milk allergy. SPT do not offer an additional predictive value, but can be used when sIgE is not available.
Keywords: Angioedema Animals Child Child; Newborn Male Milk Milk Hypersensitivity Respiratory Hypersensitivity Retrospective Studies Skin Tests Urticaria; Preschool Female Gastrointestinal Diseases Humans Immunoglobulin E Infant Infant